Development of Edible Coating from Gelatin Bone Toman Fish (Channa micropeltes) in Frozen Shrimp - Evi Fitriyani; Nani Nuraenah; Leni Lasmi; Andri Nofreena (STKIP Singkawang, 2019)
This study aims to see the storage time of frozen shrimp by using an edible coating of toman fishbone gelatin (Channa micropeltes) as a water binder that can reduce the deterioration of the quality of frozen shrimp during storage. The method used in this research is the experimental method. This research was carried out in three stages, namely: (1) making gelatin of toman fish bone and edible coating solvent (2) Characteristics of physical properties of toman fishbone gelatin (moisture content, ash content, organoleptic, amendment, water absorption); (3) Application of edible coating made from gelatin on frozen shrimp during low-temperature storage, (4) testing the quality of frozen shrimp with organoleptic parameters, WHC, cooking loss, and yield. The results of the study showed that the quality of the physical and chemical quality of the gelatin from toman fish bone was moisture content about 3.5%, about 3.5% ash content, the water of absorption about 0.00099 g/ml, and yield about 9.45%. Organoleptic results showed that gelatin powder from toman fishbone still met SNI 06-3735-1999 standards that the color of the gelatin produced was colorless to yellowish and the aroma did not smell or taste. The edible coating of frozen shrimp application with gelatin treatment resulted in decreased water content, WHC, cooking loss and organoleptic value from storage day 0 to day 30, whereas frozen shrimp with gelatin treatment resulted in water content, WHC, decreased cooking lost and organoleptic increases from storage day 0 until day 30. The best treatment results in the treatment of G2 (2% gelatin) gave a value of water content of about 33.71-82.99%, the value of WHC about 11.65-82.34%, the value of cooking losses about 2.67-6.14% and the organoleptic value is about 7.0.